Secondary developmental glaucoma - Sushmita Kaushik; Jyoti Singh; Surinder Singh Pandav (Taiwan Journal of Ophthalmology, 2023)
The basic pathophysiology of all childhood glaucoma results from impaired outflow through the trabecular meshwork. Anterior Segment Dysgeneses (ASD) are a group of nonacquired anomalies associated with secondary developmental glaucoma, characterized by impaired development of the structures of the anterior segment. Many genes impact the development of the anterior segment. The cause of the development of the abnormalities is thought to be multifactorial. Molecular research has helped our understanding of the molecular basis of ASD and the developmental mechanisms underlying these conditions. Identifying the genetic changes underlying ASD has gradually led to the recognition that some of these conditions may be parts of a disease spectrum rather than isolated anomalies. The characterization of the underlying genetic abnormalities responsible for glaucoma is the first step toward developing diagnostic and screening tests, which could identify individuals at risk for disease before irreversible optic nerve damage occurs. It is also crucial for genetic counseling and risk stratification of later pregnancies. It also aids prenatal testing by various methods allowing for effective genetic counseling. This review summarizes various ocular and systemic conditions that result in secondary developmental glaucoma and provide an overview of the phenotypes, the diagnosis and principles of management of the various disorders.